Analisis Pengajaran Membaca dan Menghafal Al-Qur’an di Pondok Pesantren Ummu Zainab Annajiyah 2 Bahrul Ulum Tambakberas Jombang dalam Perspektif Teori Behaviorisme - A’ida Masruroh; Chusnul Chotimah; Nurul Hidayah (Lembaga Yasin AlSys, 2025)
The persistently low levels of Qur’anic reading and memorization skills among intermediate-level female students remain a serious challenge in tahfidz education at Islamic boarding schools (pesantren). One approach considered effective in addressing this issue is the wahdah method, which emphasizes gradual repetition of verses until accurate memorization is achieved. This study aims to: (1) analyze the process of Qur’anic reading and memorization learning at Pondok Pesantren Ummu Zainab Annajiyah 2 Bahrul Ulum; (2) identify the role of teachers in providing stimulus, correction, and reinforcement; and (3) evaluate the effectiveness of tahfidz instruction from a behaviorist perspective. A qualitative case study approach was employed, with data collected through interviews, observation, and documentation, and analyzed using narrative descriptive techniques. The findings show that tahfidz learning is conducted systematically through stages of habituation, repetition (drill), memorization recitation (setoran), and review (muraja’ah). Teachers play an active role as providers of stimulus, correctors of recitation, and reinforcers of memorization behavior through both positive and corrective reinforcement. The application of behaviorist principles, particularly through repeated and consistent practice proved effective in improving reading skills, strengthening memorization, and fostering student discipline. The study concludes that the wahdah method, when combined with a behaviorist approach by instructors, can successfully establish optimal and sustainable learning habits. These findings highlight the importance of integrating behaviorist principles into tahfidz instruction to enhance the effectiveness and quality of Qur’anic education within the pesantren environment.